The Meaning of Denotation and Connotation in The Poem AlHawāmis 'Ala Daftar Al-Naksah by Nizār Qabbānī - Hasibuan, Azhar Ismail; Idris, Mardjoko; Herniti, Ening; Wahyudi, Jarot (Language Circle: Journal of Language and Literature, 2023)
This current paper analyses conflicts between Palestine and Israel as figure out by Nizār Qabbānī in his masterpiece poem Hawāmis 'Ala Daftar al-Naksah written in an anthology of al-A'mal al-Siyāsiyyah al-Kāmilah. In the world of Arabic Literature, Qabbānī is considered to be a famous Syrian poet. His works are related to politics, romanticism, women and voicing freedom amid patriarchal culture including the current work under discussion. This research is a type of interpretive qualitative research with data analysis methods in the form of textual analysis. The source of the research data is the poem Al-Hawāmis 'Ala Daftar Al-Naksah. The writers applied semantic method of analysis in this study, especially Gorys Keraf’s Diction and Language Style. The results of this study show the use of elusive dictions that can be understood through denotational meaning, and connotation in the poem. In terms of denotation, the poet wants to convey various problems experienced by Palestine. Second, in a connotational sense, the poet wants to convey support for Palestine and at the same time expose Israeli atrocities that are beginning to be covered up by the world, and reveal that the defeat of Arab countries against Israeli forces is not the inability of Arab countries against Israel itself but the Arab defeat is caused by the lack of unity in these Arab countries.